2022
DOI: 10.1186/s12940-022-00870-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute association between heatwaves and stillbirth in six US states

Abstract: Background Heatwaves are becoming more frequent and may acutely increase the risk of stillbirth, a rare and severe pregnancy outcome. Objectives Examine the association between multiple heatwave metrics and stillbirth in six U.S. states. Methods Data were collected from fetal death and birth records in California (1996–2017), Florida (1991–2017), Georgia (1994–2017), Kansas (1991–2017), New Jersey (199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Asamoah et al suggested that each degree increase in maternal heat exposure (measured in WBGT) in warm regions was correlated with a 27% to 42% increase in likelihood of miscarriage or stillbirth (crude OR, 1.42; 95% CI, 1.00‐2.03) 37 . Other researchers in the United States found that incremental increases in temperature were associated with an increase in the risk and incidence of stillbirth 39,40 . Additionally, an average increase of 2.8°F (1°C) over the county 97.5th percentile temperature threshold was associated with a 10% increase in risk of stillbirth (OR, 1.1; CI, 1.04‐1.17) 40 …”
Section: Heat‐related Mortality and Morbiditymentioning
confidence: 98%
See 4 more Smart Citations
“…Asamoah et al suggested that each degree increase in maternal heat exposure (measured in WBGT) in warm regions was correlated with a 27% to 42% increase in likelihood of miscarriage or stillbirth (crude OR, 1.42; 95% CI, 1.00‐2.03) 37 . Other researchers in the United States found that incremental increases in temperature were associated with an increase in the risk and incidence of stillbirth 39,40 . Additionally, an average increase of 2.8°F (1°C) over the county 97.5th percentile temperature threshold was associated with a 10% increase in risk of stillbirth (OR, 1.1; CI, 1.04‐1.17) 40 …”
Section: Heat‐related Mortality and Morbiditymentioning
confidence: 98%
“…37 Other researchers in the United States found that incremental increases in temperature were associated with an increase in the risk and incidence of stillbirth. 39,40 Additionally, an average increase of 2.8°F (1°C) over the county 97.5th percentile temperature threshold was associated with a 10% increase in risk of stillbirth (OR, 1.1; CI, 1.04-1.17). 40 Some studies suggest that the timing of exposure to temperature extremes affects risk of stillbirth.…”
Section: Stillbirthmentioning
confidence: 99%
See 3 more Smart Citations